Enlighting Mind - AAVV (Il Colle di Galileo, 2024)
Enlighting Mind is an outreach project to share notions, ideas and concepts of optics and the science of vision with the whole of society. It is also a research project to find contemporary forms to communicate science through the synergy between multiple institutions. It presents new languages and hybrid modes of expression that cross multiple disciplines, with a particular focus on the world of art.